Efficacy of growth hormone in improving the pregnancy rate in poor responders in ART - E., Nisha; H. B., Sunitha; Bhat, Vidya V.; Guddy, K. M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Poor responders impose a great challenge to ART clinicians. Research to improve their pregnancy rate is going on. This study was conducted to analyze the effect of growth hormone in poor responders in ART. Methods: This study was done from January 2015 to December 2015. It was a retrospective, single centre, cohort study in which 36 poor responders were selected and allotted into group A (18) with growth hormone and group B (18) without growth hormone. High dose of gonadotrophins was used for ovarian stimulation and antagonist protocol was followed in all patients. Group A received 4 IU of growth hormone along with usual treatment from day 2 till ovulation trigger with HCG injection, group B usual protocol. Results: Statistical analysis was done with independent T test, and p value <0.05 was considered significant. Higher number of mature oocytes and pregnancy rates were observed in growth hormone group. Number of MII oocytes was 5.8, on an average in group A and 3.7 in group B, the difference was statistically significant (p 0.0000001). Clinical pregnancy rates were 27.7% in group A and 16.6% in group B, statistical significance (p 0.02). Conclusions: Addition of growth hormone shows increase in number of oocytes retrieved and pregnancy rates in poor responders in ART patients.